1983
DOI: 10.1007/bf02214891
|View full text |Cite
|
Sign up to set email alerts
|

A reagin-like antibody in horse serum: 1. Occurrence and some biological properties

Abstract: The demonstration of a reagin-like antibody against Culicoides pulicaris extract in the serum of horses and ponies affected with recurrent seasonal dermatitis (sweet itch) is reported. This antibody can confer Prauznitz-Küstner (P-K) sensitivity on homologous skin for up to 5 days and, like human IgE, is thermolabile and susceptible to 2-mercaptoethanol reduction. It is eluted on diethylaminoethyl dextran-52 anion exchange chromatography independently of IgG, IgG(T) and IgM, and its elution characteristics ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Skin diseases such as equine summer eczema are believed to be of allergic origin because of typical, seasonal recurrent clinical signs and immediate skin reactions induced by intradermal testing with allergen extracts [4,13,27]. By assuming analogy to molecular mechanisms of human allergy and atopic disease, it has been concluded that IgE-mediated mast cell degranulation plays a major role in the pathogenesis of equine summer eczema [3,19,33]. However, the direct impact of IgE-mediated mechanisms in the disease had not previously been shown.…”
Section: Discussionmentioning
confidence: 99%
“…Skin diseases such as equine summer eczema are believed to be of allergic origin because of typical, seasonal recurrent clinical signs and immediate skin reactions induced by intradermal testing with allergen extracts [4,13,27]. By assuming analogy to molecular mechanisms of human allergy and atopic disease, it has been concluded that IgE-mediated mast cell degranulation plays a major role in the pathogenesis of equine summer eczema [3,19,33]. However, the direct impact of IgE-mediated mechanisms in the disease had not previously been shown.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have demonstrated that IgE antibodies (van der Haegen et al 2001;Wilson et al 2001) and IgE-mediated reactions Mathews et al 1983;Halldorsdottir et al 1989;Fadok and Greiner 1990;Fadok and Foil 1990;Anderson et al 1993) are often involved in the pathogenesis of IBH.…”
Section: Introductionmentioning
confidence: 99%
“…The original description of this condition as an allergic response to the bites of Culicoides spp. was made 60 years ago in Australia by Riek (58,59); the presence of a reagenic antibody specific for Culicoides antigens was subsequently demonstrated in serum of affected horses (60). During the ensuing decades, several studies in diverse continents replicated these findings and hypersensitivity of horses to Culicoides bites became recognized as one of the commonest skin conditions to affect horses worldwide (48,52,(61)(62)(63)(64)(65).…”
Section: Insect Bite Hypersensitivitymentioning
confidence: 92%